Inhibitory effects of curculigoside on human liver cytochrome P450 enzymes. (3rd October 2017) - Lang, Jixiao; Li, Wei; Zhao, Jingming; Wang, Kaiyou; Chen, Dexi
Abstract: 1. Curculigoside possesses numerous pharmacological activities, and however, little data available for the effects of curculigoside on the activity of human liver cytochrome P450 (CYP) enzymes. 2. This study investigates the inhibitory effects of curculigoside on the main human liver CYP isoforms. In this study, the inhibitory effects of curculigoside on the eight human liver CYP isoforms 1A2, 2A6, 2E1, 2D6, 2C9, 2C19, 2C8, and 3A4 were investigated in human liver microsomes. 3. The results indicated that curculigoside could inhibit the activity of CYP1A2, CYP2C8, and CYP3A4, with IC50 values of 15.26, 11.93, and 9.47 μM, respectively, but that other CYP isoforms were not affected. Enzyme kinetic studies showed that curculigoside was not only a noncompetitive inhibitor of CYP1A2, but also a competitive inhibitor of CYP2C8 and CYP3A4, with Ki values of 5.43, 3.54, and 3.35 μM, respectively. In addition, curculigoside is a time-dependent inhibitor for CYP1A2, with kinact / KI values of 0.056/6.15 μM −1 min −1 . 4. The in vitro studies of curculigoside with CYP isoforms suggest that curculigoside has the potential to cause pharmacokinetic drug interactions with other coadministered drugs metabolized by CYP1A2, CYP2C8, and CYP3A4. Further in vivo studies are needed in order to evaluate the significance of this interaction.